Heart failure and Alzheimer′s disease. (1st August 2014) - Cermakova, P.; Eriksdotter, M.; Lund, L. H.; Winblad, B.; Religa, P.; Religa, D.
Abstract: It has recently been proposed that heart failure is a risk factor for Alzheimer′s disease. Decreased cerebral blood flow and neurohormonal activation due to heart failure may contribute to the dysfunction of the neurovascular unit and cause an energy crisis in neurons. This leads to the impaired clearance of amyloid beta and hyperphosphorylation of tau protein, resulting in the formation of amyloid beta plaques and neurofibrillary tangles. In this article, we will summarize the current understanding of the relationship between heart failure and Alzheimer′s disease based on epidemiological studies, brain imaging research, pathological findings and the use of animal models. The importance of atherosclerosis, myocardial infarction, atrial fibrillation, blood pressure and valve disease as well as the effect of relevant medications will be discussed.